Avian and crocodilian eggshells from the upper Barremian site of Vadillos-1 (Lower Cretaceous, Cuenca province, Spain). (May 2018) - Bravo, Ana M.; Sevilla, Paloma; Barroso-Barcenilla, Fernando
Abstract: The new upper Barremian microfossil site of Vadillos-1 (Lower Cretaceous, Beteta Gorges, Cuenca province, Spain) has yielded a rich fossil assemblage consisting of numerous eggshell fragments along with diverse skeletal remains of fishes, amphibians, turtles, crocodyliforms and dinosaurs. Crocodilian eggshells constitute the main fraction of the eggshell assemblage which includes abundant material belonging to the oofamily Krokolithidae, as well as a new type of crocodilian eggshells ( Neokrokolithes trigonalis oogen. et oosp. nov.) characterised by a type of ornamentation and microstructure of the basal knobs not described before. Few fragments of the oospecies cf. Mycomorphoolithus kohringi, attributed to non-eusuchian crocodylomorphs, have been also found in this site thus expanding the record of this oospecies to the upper Barremian. The eggshell assemblage has also yielded the first record of avian eggshells ( Tristratioolithus minuta oogen. et oosp. nov.) from the Lower Cretaceous of Europe. Comparisons with Lower Cretaceous avian eggshells suggest its possible attribution to Enantiornithes. The tiny eggshell fragments assemblage found at Vadillos-1 site is representative of a small sized fauna. Besides, the diversity appears strongly biased with >90% of the eggshells belonging to crocodilians and approximately 9% to Aves. As established for similar outcrops, this bias may reflect differences in preservation of eggshell types or represent, at least in part, a wetland ground nesting site.